Analisis Profitabilitas Bank Umum Syariah Go Public Pada Masa Covid-19 - Halim, Fajriyah Salsabila; Putri, Elita Ichwan; MarfuÔÇÖ, Umar (Al-bank: Journal of Islamic Banking and Finance, 2022)
This study aims to analyze the level of profitability of Islamic Commercial Banks that have Go Public during the Covid-19 pandemic. These conditions can lead to various problems that can trigger the profitability of a bank's financial performance. The method used in this research is quantitative with horizontal analysis techniques with secondary data sources. The results obtained from this study indicate that the level of profitability of Islamic commercial banks which are the object of research has a level of profitability which shows an increase as well as a decrease due to the Covid-19 pandemic which affects the soundness of the bank. This research is limited to the financial performance before the pandemic and during the pandemic as well as the profitability level of Islamic Commercial Banks that Go- So that the results of this study can be used as guidelines in making and formulating policies.